# If a polynomial is divided by (x-a) and the remainder equals zero then (x -a) is a factor of the polynomial. true or false

The Factor theorem states that for any polynomial f(x) if f(c)=0 then x-c is a factor of the polynomial f(x).

If any polynomial f(x) is divided by x-a and remainder is 0 that means f(a)= 0 .In other words we can say x-a is a factor of the polynomial f(x).So the statement :If a polynomial is divided by (x-a) and the remainder equals zero then (x -a) is a factor of the polynomial is True.

## Related Questions

(x + p)(x + q)

x^2 + px + 1x +pq

x^2 +

**(p+q)x**+ pq

Hope this answers the question. Have a nice day.

For f(x)=2x+1 and g(x)=x^2-7, find (f-g)(x)

(f-g)(x)=2x+1-(x^2-7)

(f-g)(x)=2x+1-x^2+7

(f-g)(x)= -x^2+2x+8

TopAcademicTutors.Com

Expert Assignment Help for students who have pending assignments.

For 10$ a page, you can get your written essay.

Which test point holds true for y − 2x ≤ 1? (0, 2) (-2, 4) (1, 4) (5, 0)

y − 2x ≤ 1

0 - 2(5) ≤ 1

0-10 ≤ 1

-10 ≤ 1

Hope this answer helps.

True or false Volume can be measured in liters or cubic meters.

What is f(x) = 2x2 + 28x – 5 written in vertex form?

f(x) = 2x^2 + 28x – 5

f(x) = 2(x^2 + 14x) – 5

f(x) = 2(x^2 + 14x + 49) – 5 - 98

**f(x) = 2(x + 7)^2 – 103**

Hope this answers the question. Have a nice day.

TopAcademicTutors.Com

Expert Assignment Help for students who have pending assignments.

For 10$ a page, you can get your written essay.

Given f(x)=17-x^2, what is the average rate of change in f(x) over the interval [1, 5]?

average rate of change is

(f(5) - f(1))/(5 - 1) =

(17 - 5^2 - (17 - 1^2))/4 =

(17 - 25 - 17 + 1)/4 =

So the answer for this problem is

**-6**

I hope my answer helped you. Feel free to ask for more questions.

f(x) = P(1 + r)^x

Now we can solve.

Given:

P = 2000

r = -0.06

f(x) = 2000 (1 - 0.06)^x

= 2000 (0.94)^x

2000 (0.94)¹² =

2000 (0.476) =

The answer is

**951.8 square kilometers.**

TopAcademicTutors.Com

Expert Assignment Help for students who have pending assignments.

For 10$ a page, you can get your written essay.

**The answer is**

BThe vertex of the graph is (5, –37).

B

**The parabola has a minimum.**

C

C

**D**The parabola opens up.

A transversal must intersect two or more parallel lines true or false

The answer is false.

TopAcademicTutors.Com

Expert Assignment Help for students who have pending assignments.

For 10$ a page, you can get your written essay.

**Answer:**

**Option 2,3 and 4 are correct.**

**Step-by-step explanation:**

**To find : **Which terms could be used as the first term of the expression below to create a polynomial written in standard form? Check all that apply.

**Solution : **

The polynomials in standard form is written from higher degree to lower degree** i.e. in descending order.**

**The given polynomial has degree 6**: , and it can be ordered respect any of the two variables either r or s.

Adding a new term as first term needs to have degree equal or greater than 6.

**1)** cannot use as first term because its degree is less than 6.

**2)** it can be use as degree is 9.

is the standard form.

**3) ** it can be use as degree is 10.

is the standard form.

**4) ** it can be use as degree is 6.

is the standard form.

**Therefore, Option 2,3 and 4 are correct.**

What is the range of the function f(x) = 3x2 + 6x – 9

f(x)=3x^2-6x+1

My solution is:

The domain is all real numbers--there are no restrictions like a square root or variable in the denominator

this is a U shape parabola and you want to find the bottom point, it is at the vertex

x=-b/2a =- (-6) /2 (3) =1

f(1) =3(1)^2 -6(1) +1 =3-6+1 =-2

the minimum is (1, -2)

so the range is all real numbers >= -2

By examining my solution, you could just answer the problem on your own! I hope it helps!

Which of the binomial is a factor of this trinomial x2-7x-44?

x^2-7x-44

x -11

x +4

(x-11)(x+4)

TopAcademicTutors.Com

Expert Assignment Help for students who have pending assignments.

For 10$ a page, you can get your written essay.

**Answer:**

D

**Step-by-step explanation:**

She showed that f(n) - f(n - 1) was a constant difference.

The definition of an arithmetic sequence is** the difference between consecutive terms is constant, aka common difference.**

TopAcademicTutors.Com

Expert Assignment Help for students who have pending assignments.

For 10$ a page, you can get your written essay.

**Answer:**

A) -4c^2 + 4c + 6

**Step-by-step explanation:**

The given polynomial is 2 + 7c – 4c^2 – 3c + 4

Add the like terms.

2 + 4 + 7c - 3c -4c^2

= 6 + 4c - 4c^2

Write it in a standard form

= -4c^2 + 4c + 6

Answer is A) -4c^2 + 4c + 6

Hope this will helpful.

Thank you.

Unordered polynomial is

7x3y3 + 4 - 11x5y2 - 3x2y

Polynomial in descending order looks like this

-11x5y2 + 7x3y3 - 3x2y + 4

Degree of the second term is 5 ( because of x5 )

Which of the following is a factor of 2x4 + 22x3 + 60x2? 2x3 x4 x + 4 x + 5

The correct answer is **Option D, **or **X+5**. I hope I answered this question to your satisfaction Have a nice day!

TopAcademicTutors.Com

Expert Assignment Help for students who have pending assignments.

For 10$ a page, you can get your written essay.

A = (x+3)^2 = x^2+6x+9

Because for so solving the additive inverse of 9xy² + 6x²y - 5x³

-1(9xy² + 6x²y - 5x³) then it will turn to this ⇒ (-1)(9xy²) + (-1)(6x²y) + (-1)(-5x³)

**-9xy² - 6x²y + 5x³**is the additive inverse of the given polynomial.

Your answer is 20.71

If you want more than it is 20.71231517

TopAcademicTutors.Com

Expert Assignment Help for students who have pending assignments.

For 10$ a page, you can get your written essay.

**1) The answer is: [B]: r = 5 .**

**__________________________**

**Explanation:**

**___________**_______________

Given: 7r − 7 = 2r + 18 ; Round your answer to the nearest tenth, if necessary.

____________________________

Since "r" is the only variable given, let us assume we want to solve for "r" (instead of "x").

___________________________

→ Subtract "2r" from EACH SIDE of the equation; and & add "7" to EACH SIDE of the equation:

_____________

→ 7r − 7 − 2r + 7 = 2r + 18 − 2r + 7 ; to get: → 5r = 25 ;

_____________

→ Now, divide EACH SIDE of the equation by "5"; to isolate "r" on one side of the equation; and to solve for "r" :

______________

→ 5r / 5 = 25 / 5 → r = 5 → which is: "Answer choice: [B]".

_________________

**Let us check our answer, by plugging in "5" for "r" in the original equation:**

_________________

→ 7r − 7 = 2r + 18 ; → 7(5) − 7 =? 2(5) + 18? ;

______________________

→ 35 − 7 =? 10 + 18 ?; → 28 =? 28? Yes!

______________________

**2) The answer is: [D]: x = 2 .**

**_____________**

**Explanation:**

_____________

Given: 2x + 12 = 18 − x ; Solve for "x" (round to nearest tenth, if necessary).

_______________

→ Add "x" to EACH SIDE of the equation, & subtract "12" from EACH SIDE of the equation: → 2x + 12 + x − 12 = 18 − x + x − 12 ;

______________

→ To get: 3x = 6 ; → Divide EACH SIDE of the equation by "3";

to isolate "x" on one side of the equation; and to solve for "x":

_____________

→ 3x / 3 = 6 / 3 ; → x = 2 ; which is: "Answer choice: [D]".

______________

**Let us check our answer, by plugging in "2" for "x" in the original equation:**

________________

→ 2x + 12 = 18 − x ; → 2(2) + 12 =? 18 − 2 ?

________________

→ 4 + 12 =? 18 − 2 ? ; → 16 =? 16? Yes!

________________________________

**3) The answer is: [A]: x = -3 .**

**_____________**

**Explanation:**

________________

Given: 8x − 3 = 15x + 18 ; Solve for "x". Round your answer to the nearest tenth, if necessary.

_________________

→ Subtract "8x" from EACH SIDE of the equation, & add "3" to EACH SIDE of the equation:

_______________

→ 8x − 3 − 8x + 3 = 15x + 18 − 8x + 3 ; to get:

_______________

→ 0 = 7x + 21 ; → Subtract "21" from EACH SIDE of the equation;

_______________

→ 0 − 21 = 7x + 21 − 21 ; to get:

_______________

→ -21 = 7x ; Now divide EACH SIDE of the equation by "7";

to isolate "x" on one side of the equation; & to solve for "x":

_______________

→ = -21 / 7 = 7x / 7 ; → -3 = x ; which is "Answer choice: [A]."

**_________________**

**Let us check our answer, by plugging in "-3" for "x" in the original equation:**

________________

→ 8x − 3 = 15x + 18 ; → 8(-3) − 3 =? 15(-3) + 18 ?;

________________________

→ -24 − 3 =? -45 + 18 ? ; → -27 =? -27? Yes!

**___________________________**

**4) The answer is: [C]: y = 11 .**

**_____________**

**Explanation:**

**____________**

Given: 6y − 6 = 4y + 16 ; Solve for "y"; Round to the nearest tenth, if necessary.

____________

(Note: Since "y" is the only variable given; assume we are to solve for "y" instead of "x").

____________

→ Subtract "4y" from EACH SIDE of the equation, & add "6" to EACH SIDE of the equation; → 6y − 6 − 4y + 6 = 4y + 16 − 4y + 6 ; to get:

_______________

→ 2y = 22 ; Now, divide EACH SIDE of the equation by "2"; to isolate "y" one side of the equation; and to solve for "y" ;

_______________

→ 2y / 2 = 22 / 2 ; → y = 11 → which is "Answer choice: [C]".

**_______________________________**

**Let us check our answer, by plugging in "11" for "y" in the original equation:**

**___________________**

→ 6y − 6 = 4y + 16 ; → 6(11) − 6 =? 4(11) + 16 ?

_______________________

→ 66 − 6 =? 44 + 16 ? → 60 =? 60 ? Yes!

**__________________**

**5) The answer is: [B]: x = -11 .**

**_____________________**

**Explanation:**

**_________________**

Given: 3(x − 4) = 5(x + 2) ; Solve for "x". Round to the nearest tenth, if necessary.

**___________**

**→Note the "distributive property of multiplication":**

**_____________**

**a*(b + c) = ab + ac ; and: a*(b − c) = ab − ac ;**

**_______________**

→ Let us expand EACH SIDE of our given equation.

→Start with the "left-hand side":

____________

3(x − 4) = (3*x) − (3*4) = 3x − 12;

______________________________

→Now let us expand the "right-hand side" of the given equation:

____________

→ 5(x + 2) = (5*x) + (5*2) = 5x + 10 ;

______________

→Now, we can rewrite the original equation:

_______________

→ 3(x − 4) = 5(x + 2) ; by substituting the expanded values for EACH SIDE of the question: → 3x − 12 = 5x + 10 ;

__________________

→ Subtract "3x" from EACH SIDE of the equation; and add "12" to EACH SIDE of the equation: → 3x − 12 − 3x + 12 = 5x + 10 − 3x + 12 ; to get:

________________

→ 0 = 2x + 22; → Now subtract "22" from EACH SIDE of the equation:

______________

→ 0 − 22 = 2x + 22 − 22 ; to get: → -22 = 2x ;

__________

→ Divide EACH SIDE of the equation by "2"; to isolate "x" on one side of the equation; & to solve for "x" ;

_____________

→ -22 / 2 = 2x /2 ; → -11 = x ; which is "Answer choice: [B]".

______________

**Let us check our answer, by plugging in "-11" for "x" in the original equation:**

**___________**

→ 3(x − 4) = 5(x + 2) ; → 3(-11 − 4) =? 5(-11 + 2) ? ;

_______________________

→3(-15) =? 5(-9) ? ; → -45 =? -45 ? Yes!

**_____________________________________________**

**Hope these answers and explanations are helpful. Best of luck!**

TopAcademicTutors.Com

Expert Assignment Help for students who have pending assignments.

For 10$ a page, you can get your written essay.

f ( x ) = √( 1 - x²), g ( x ) = - 2

= - 50/3

My = p ∫ x * ( f ( x ) ) dx

My = p ∫ x ( √(1+x²)) dx

Substitution: 1 - x² = u, x dx = - du/2

**M x = - 50/3, M y = 0**

M ≈ 5 * 6.3 ≈ 31.2

x = M y / M = 0 / 31.5 = 0

y = M x / M = -50/3 : 31.5 ≈ - 0.529

The center of mass is

**( 0, -0.529 )**

we have

Combine like terms

therefore

__the answer is the option C__

He combined the terms and incorrectly

TopAcademicTutors.Com

Expert Assignment Help for students who have pending assignments.

For 10$ a page, you can get your written essay.